Analisis Hasil Belajar PAI Menggunakan Media Pembelajaran Ular Tangga Pada Siswa dan Siswi Kelas IV di SD Negeri 15 Lansat Kadap - Ramadhan, Syahrul; N, Nurbainis; Monia, Fenny Ayu (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to describe the design of media development and determine the effectiveness of media development. This research includes research on development using the development method. The development methods used are interviews, tests, and documentation. Data were analyzed using qualitative descriptive analysis techniques. Where in the results of the study it can be seen that the support for the game of snakes and ladders was developed using development methods such as analysis, design, which in this case when analyzing the development of this field, students are excited to le jiarn PAI again, initially they feel bored learning PAI, which means poor communication. effective occurs when playing the game of snakes and ladders while learning PAI in class. So, the Snakes and Ladders game aims to improve the learning outcomes of fifth grade students in terms of PAI knowledge and skills